2012
DOI: 10.1038/srep00806
|View full text |Cite
|
Sign up to set email alerts
|

APOBEC3B can impair genomic stability by inducing base substitutions in genomic DNA in human cells

Abstract: Human APOBEC3 proteins play pivotal roles in intracellular defense against viral infection by catalyzing deamination of cytidine residues, leading to base substitutions in viral DNA. Activation-induced cytidine deaminase (AID), another member of the APOBEC family, is capable of editing immunoglobulin (Ig) and non-Ig genes, and aberrant expression of AID leads to tumorigenesis. However, it remains unclear whether APOBEC3 (A3) proteins affect stability of human genome. Here we demonstrate that both A3A and A3B c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
100
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(105 citation statements)
references
References 50 publications
4
100
0
1
Order By: Relevance
“…This is considered to be due to an increased transition from dC to dT and the resultant increased mutation frequency (5). These mutations were commonly found in oncogenes transcribed in tumor cells (17); for example, in lymphoma cell lines, overexpression of APOBEC3B produced an increase in dC to dT mutations in c-Myc (18). In the present study, it was shown that APOBEC3B was present in all of the fetal leptomeninges, 88% of WHO grade I, 100% of grade II and 83% of grade III meningiomas tested, without differences between grades.…”
Section: Discussionsupporting
confidence: 46%
“…This is considered to be due to an increased transition from dC to dT and the resultant increased mutation frequency (5). These mutations were commonly found in oncogenes transcribed in tumor cells (17); for example, in lymphoma cell lines, overexpression of APOBEC3B produced an increase in dC to dT mutations in c-Myc (18). In the present study, it was shown that APOBEC3B was present in all of the fetal leptomeninges, 88% of WHO grade I, 100% of grade II and 83% of grade III meningiomas tested, without differences between grades.…”
Section: Discussionsupporting
confidence: 46%
“…Other AID/APOBECs have been shown to induce DNA damage and somatic mutations [30,54,55], and they are involved in kataegis, clusters of mutations observed in some cancer genomes [29,32,35,56,57]. An AID/APOBEC mutational signature can be observed in genes highly mutated in cancer [39] and in cancer genomes and exomes [31,[33][34][35]58].…”
Section: Aid/apobec Mutational Signature In Esophageal Adenocarcinomasmentioning
confidence: 99%
“…However, A3A has also been shown to be genotoxic under conditions of overexpression (22,23,26) and to mutate genomic DNA (24,25). CD14 ϩ cells are known to express high levels of A3A upon type I IFN induction (4,6,7), suggesting that these cells must either have a mechanism for regulating A3A activity or be subject to its genotoxic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpressed A3A has been shown to cause chromosomal DNA damage and mutation (22)(23)(24)(25)(26) as well as disruption of the cell cycle (22,26). Expression of A3A in a cell threatens genomic integrity, suggesting that uncontrolled activation of this immune defense molecule would have undesirable consequences.…”
mentioning
confidence: 99%